Witnessing inter-parental violence in childhood and help-seeking behaviours in violence against women in Peru - Juan Carlos Bazo-Alvarez; Anthony Copez-Lonzoy; Miguel Ipanaqué-Zapata; Janina Bazalar-Palacios; Elizabeth López Rivera; Elaine C. Flores-Ramos (BMC, 2024)
Abstract Background Violence against women (VAW) severely impacts their physical and mental health. In some cultures, women can normalize certain types of violence if they were linked to home models in childhood and, eventually, do not seek for help in adulthood. We aimed to determine, in Peruvian women, (1) the association between witnessing violence in their family of origin and VAW experienced in adulthood, (2) the extent to which women who have experienced VAW seek some help, and (3) identify VAW prevalence by Peruvian region. Methods Cross-sectional study of secondary data obtained from the 2019 National Demographic and Family Health Survey (ENDES). The outcome was VAW (psychological, physical and sexual violence), whereas the exposure was witnessing violence in the home of origin. Help-seeking behavior was a secondary outcome, for which VAW was the exposure. Prevalence ratios (PR) were estimated to assess both associations, unadjusted and adjusted for covariates (aPR). Results Data from 14,256 women aged 15 to 49 years were analysed. 51.5% reported having experienced VAW and 43.8% witnessed violence in the home of origin during childhood. Witnessing inter-parental violence in childhood was associated with psychological violence aPR = 1.25 (95% CI: 1.17-1.33), physical aPR = 1.52 (95% CI: 1.38-1.67), and sexual aPR = 1.99 (95% CI: 1.57-2.52). Women who have experienced both types of violence (physical and sexual) were more likely to help-seeking (aPR = 1.30, 95% CI: 1.14-1.50) than women suffering only one type of violence. Conclusion Women who reported having witnessed home violence in their childhood are more likely to experience Violence Against Women (VAW) by their current partner. Physical and sexual violence with a current partner was more associated with witnessing inter-parental violence in childhood, and when physical and sexual violence jointly occurred women were more help-seeking. The southern region of Peru is identified as an area of high vulnerability for women. It is crucial to promote educative and community-based programs aimed at the prevention and early recognition of VAW.